Advantages of Tailing Disposal by Thickened Discharge - E. I. Robinsky (Canadian Institute of Mining, Metallurgy and Petroleum, 1976)
"This paper describes a new, proven approach for tailing disposal. Not only is the disclosed system less damaging to the environment, it is also less costly to operate, to close down and maintain in perpetuity. The basic concept is to discharge thickened tailing from one permanent location.This creates a conical or hill-like deposit which:(1) requires lower perimeter dykes for equivalent storage capacity;(2) eliminates decant towers and decant lines;(3) requires no steep dams built of tailing;(4) is stable:(5) requires only a small pond outside the deposit;(6) decreases pollution of the surrounding environment by water seepage and deflation; and(7) simplifies abandonment and ""closing-down"" operations.The approach is made possible by the fact that, at a sufficiently high ratio of solids to water, tailing material can be made to accumulate at slopes of 5 or 6 per cent -- considerably steeper than possible by traditional methods using low solids-to-water ratios. To achieve the necessary solids-water ratio (35 to 60 per cent), it may be necessary to install a thickener. It is expected, however, that at many concentrators it may be possible to discharqe relatively clear plant water through a line separate from the tailing line, thus reducing the load on the thickener."